Trials Comparing Percutaneous And Surgical Myocardial Revascularization: A Review - De Palo, Micaela; Quagliara, Teresa; Dachille, Annamaria; Carrozzo, Alessandro; Giardinelli, Francesco; Mureddu, Simone; Mastro, Florinda; Rotunno, Crescenzia; Paparella, Domenico (Reviews on Recent Clinical Trials, 2019)
Introduction: Ischemic heart diseases are the major leading cause of death worldwide. Revascularization procedures dramatically reduced the overall risk for death related to acute coronary syndromes. Two kinds of myocardial revascularization can grossly be outlined: percutaneous coronary intervention (PCI) and surgical coronary artery bypass graft intervention (CABG). The net clinical benefit coming from these two kinds of procedures is still under debate. Methods: We have traced the state-of-the-art background about myocardial revascularization procedures by comparing the most important trials dealing with the evaluation of percutaneous interventions versus a surgical approach to coronary artery diseases. Results: Both PCI and CABG have become effective treatments for revascularization of patients suffering from advanced CAD. The advance in technology and procedural techniques made PCI an attractive and, to some extent, more reliable procedure in the context of CAD. However, there are still patients that cannot undergo PCI and have to be rather directed towards CABG. Conclusion: CABG still remains the best strategy for the treatment of multiple vessel CAD due to improved results in term of survival and freedom from reintervention. Anyway, a systematic, multidisciplinary approach to revascularization is the fundamental behaviour to be chased in order to effectively help the patients in overcoming its diseases. The creation of the “heart team” seems to be a good option for the correct treatment of patients suffering from stable and unstable CAD.
Keywords: CABG